STRATEGI PEMASARAN TELUR AYAM RAS DI DESA PASIR UTAMA KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Ferdian, M Yogi (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
This study aims to determine the marketing channels of eggs and eggs marketing strategies. The method used in this study is a qualitative research method by observation, interview and documentation. Based on the results of this research note egg marketing channel is through the manufacturer to the dealer and then to the middle stalls and consumers. Based on the results of internal analysis using IFE obtained a score of 2.85 and an external analysis results using EFE obtained a score of 2.40. Thus putting the marketing of eggs are in quadrant V, a strategy that can be applied is intensive strategy, the strategy of market penetration, market development, and product development.